Second Five Year Plan Fisheries Vindhya Pradesh Government of Vindhya Pradesh - Planning Commission (Planning Commission, 1955)
The Department came into existence during the First Five Year Plan in September, 1952. 4902-34 acres of water area hade been surveyed and 34 species of fishes recorded 171-8 acres have been stocked with 3,43,544 large sized carp fingerlings during the years 1953-54 & 1954-55. 5,50,000 carp fry is being reared in departmental rearing tanks and nearly 135 acres would be stocked in the year 1955-56. The tanks stocked in the year 1953-54, with 1,38,264 fingerlings have fetched revenue of Rs, 33,100 and it to anticipated that during the year 1956-57 there will be an additional fish production of 2,250 mds of fish valued at Rs, 45,000. Five Zoology Graduates were sent for training at the Central Inland Fisheries Research Station, Calcutta.
Directorate of Animal Husbandry & Fisheries, Vindhya Pradesh Rewa
Government of Vindhya Pradesh
Keywords: Conservation; Exploitation; Development Loans to Fishermen; Gram Panchayat Co-operative Societies; Building Programme; Allowance & Honoraria; Continent employees; Reclamation and Stocking; Supply of fishery requisition; Maturing of nurseries; Maintenance of Laboratory; Artificial food